The Effect of Quality Audit, Earning Management and Good Corporate Governance on Financial Performance: Empirical Study on Food and Beverage Companies Listed on the IDX for the 2019-2023 Period - nazwa ashila nazwa; Indupurnahayu Indupurnahayu; M Anwar Masruri (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
This study assesses the extent to which audit quality, earnings management, and corporate governance practices shape firms’ financial performance. The investigation centers on food-and-beverage companies listed on the Indonesia Stock Exchange between 2019 and 2023. Employing a quantitative approach, the research relies on purposive sampling, yielding 26 firms as the analytical units. Data were processed with Statistical Product and Service Solutions (SPSS), and relationships among variables were examined through multiple linear regression. The results indicate that audit quality and earnings management exert a significant positive influence on financial performance, whereas good corporate governance does not display a meaningful positive effect according to the partial (t-test) analysis. Keywords:Audit Quality; Earning Managemnet; Good CorporateGovernance and Financial Performance